Effects of a Family-Centered Care Promotion Program on Self-Management Behaviors in Patients Undergoing Continuous Ambulatory Peritoneal Dialysis - Rueangphut, Pimpawan; Samdaengsarn, Dalima; Jitbantad, Waranya (Journal of Nursing and Public Health Research, 2025)
This quasi-experimental researchstudy with a one-group pretest-posttest aimed to study the effect of family care promoting program on self-management behaviors among patients with continuous ambulatory peritoneal dialysis. The simple random sampling consisted of 23 participants. Research tool was the family care promoting program on self-management behaviors, developed by the researcher. Data collection instruments included a personal information questionnaire, a self-management behavior assessment, and a self-management observer. General data were analyzed using descriptive statistics and wilcoxon signed rank test. The findings showed that, after experiment, the participants showed a statistically significant increased their mean score on self-management behavior and observed self-management before the experiment (p-value < .001). The results demonstrated that a family care promoting program on self-management behaviors effectively improves self-management behavior. Nurse and healthcare teams can apply this program to services in medical facilities and communities that require continuous home-based follow-up care.